Financial Inclusion and Psychological Wellbeing: A Systematic Review - Atta, Abdulmalik (The Indonesian Institute of Science and Technology Research, 2024)
The focus of this study is to evaluate the literature on the connections between financial inclusion and psychological wellbeing through a systematic review. The results implied that the literature utilized financial services, capacity, resilience, and financial awareness to measure financial inclusion. Indicators of psychological well-being include contentment and happiness, good housing and health, ownership of assets, financial security, and accessibility to sanitation services. Financial inclusion results in greater financial wellness, which benefits psychological wellbeing. Therefore, there is need for proactive measures to ensure that the financially excluded people are integrated into the financial system, which will improve their psychological wellbeing.